Mechanical and imaging properties of a clinical-grade kidney phantom based on polydimethylsiloxane and elastomer - Kamal, Izdihar; Abdul Razak, Hairil Rashmizal; Abdul Karim, Muhammad Khalis; Mashohor, Syamsiah; Ying, Josephine Chyi Liew; Low, Yiin Jian; Zaaba, Nur Atiqah; Mazlan, Norkhairunnisa; Mohd Rafi, Nur Athirah Syima (Multidisciplinary Digital Publishing Institute, 2022)
Medical imaging phantoms are considered critical in mimicking the properties of human tissue for calibration, training, surgical planning, and simulation purposes. Hence, the stability and accuracy of the imaging phantom play a significant role in diagnostic imaging. This study aimed to evaluate the influence of hydrogen silicone (HS) and water (H2O) on the compression strength, radiation attenuation properties, and computed tomography (CT) number of the blended Polydimethylsiloxane (PDMS) samples, and to verify the best material to simulate kidney tissue. Four samples with different compositions were studied, including samples S1, S2, S3, and S4, which consisted of PDMS 100%, HS/PDMS 20:80, H2O/PDMS 20:80, and HS/H2O/PDMS 20:40:40, respectively. The stability of the samples was assessed using compression testing, and the attenuation properties of sample S2 were evaluated. The effective atomic number of S2 showed a similar pattern to the human kidney tissue at 1.50 × 10−1 to 1 MeV. With the use of a 120 kVp X-ray beam, the CT number quantified for S2, as well measured 40 HU, and had the highest contrast-to-noise ratio (CNR) value. Therefore, the S2 sample formulation exhibited the potential to mimic the human kidney, as it has a similar dynamic and is higher in terms of stability as a medical phantom.